The Relationship Between Air Pollution Exposure And The Incidence Of Chronic Respiratory Disease: A Case Study In An Urban Area - Sari, Fitria Kusuma (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
This study aims to investigate the causal relationship between air pollution and the incidence of respiratory tract diseases in residents of Bogor City, West Java, Indonesia. Bogor City is a densely populated city with significant levels of air pollution due to industrial activities, transportation, and people's lifestyles. This study uses the causality analysis method to identify the relationship between air pollution and respiratory diseases. Data on air pollutant concentrations (particulate matter PM2.5, SO2, NO2) and the number of respiratory tract disease cases were taken from available sources, such as the Bogor City Environment Agency and local public health centers. The results showed a significant causal relationship between air pollution and the incidence of respiratory diseases. Particulate concentrations of PM2.5, SO2, and NO2 have a detrimental impact on the health of residents. The study also highlighted the different effects of air pollution on different population groups, such as children, the elderly, and individuals with compromised health. These findings provide a deeper understanding of the health risks faced by Bogor City residents due to air pollution. In order to improve air quality and reduce its adverse health impacts, this study suggests the need for effective policy measures. Such measures include improved control of industrial and vehicular emissions, increased public awareness of the impacts of air pollution, and improved access to health services related to respiratory diseases. This study confirms the existence of a causal relationship between air pollution and the incidence of respiratory diseases in Bogor City residents. The findings provide a strong basis for taking more effective preventive and intervention measures to address air pollution and public health issues in urban areas.